BUKU SAKU SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA EKONOMI DI PROGRAM STUDI PENDIDIKAN AKUNTANSI FKIP UNIVERSITAS PGRI PALEMBANG - Depi Pramika; Merlyn Widalismana (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This research aims to; 1) developing a validity book on the economic mathematics in the Accounting Education Program of FKIP University PGRI Palembang 2) developing a pocketbook on economic mathematics at the FKIP University PGRI Palembang Accounting Education Study Program which has been tested for practicality 3) developing economic mathematics pocketbooks in Accounting Education Study Programs FKIP University PGRI Palembang has been developed towards student learning outcomes. The method used in this study is the Development Research or Research and Development (R & D). The results of the study show; 1) pocketbooks of economic mathematics as learning media developed for student learning have been validated with an average of 4.2 very valid criteria based on the assessment of material and language experts, and an average of 4 based on media experts 2) with a percentage of 100%, based on the small group stage and the one to one phase of the very practical categorized economic mathematics pocketbook 3) the results of the field test stage showed that the pocketbook of economic mathematics as a learning medium that had been developed had a potential effect on student learning outcomes with an average score of 7.9 good categories once, and also has a potential effect on student learning activeness with a score of 42.3 very active categories.Keywords: Development, Pocketbook, Economic Mathematics, Learning Media